SOSIALISASI DAMPAK ANEMIA BAGI REMAJA DAN UPAYA PENCEGAHANNYA - Gustina, Irwanti; E.U Djami, Moudy; Yuria R.A, Mella; Chairiyah, Royani (Jurnal Abdi Insani, 2025)
The incidence of anemia in adolescents globally is still relatively high. Anemia is a condition in which the component in the blood, namely hemoglobin, is less than normal. Adolescent girls have a ten times greater risk of suffering from anemia compared to adolescent boys. This is because adolescent girls menstruate every month and are in the process or growth period so they need more iron intake. The purpose of this activity is to socialize the impact of anemia on adolescents and efforts that can be made to prevent it. The method used involved 203 students in grades X and XI of SMK Kesehatan Mulia Karya Husada located in South Jakarta. The socialization activity lasted for 90 minutes which was packaged in a pre-test and post-test, followed by checking the Hb levels of the participants who attended. The evaluation results showed that in the Pre-test, students' knowledge about anemia and its impacts was 42.5%, while in the Post-test it was 95.5%. Thus, there was an increase in knowledge from the results of the socialization of the impact of anemia on adolescents and efforts to prevent it. From this activity, the community service also obtained data on 16.7% of adolescent girls with mild to moderate anemia. This is a note for the author that cases of anemia in adolescents need to be watched out for and need special attention in their handling. By preventing one teenage girl from Anemia, it means we save a prospective mother or child from the risk of stunting and other reproductive emergency risks in the future.